Comparative Analysis of Optimizer Methods for Machine Learning Algorithm using Search Keyword Ad Data - Park, Hyunhee; Ji, Minjun; ., . (International Journal of Engineering and Technology, 2018)
A searching for specific keywords through an online web searching platform (e.g., Google or Naver) is one of the most popular search mechanisms. Therefore, an advertisement on the online web searching platform has become one of the representative advertising marketing mechanisms. In order to advertise a specific keyword, it is necessary to pay the web-search-word to the online web searching platform and participate in the bid system. However, since the ads of online web searching platform are operated privately, it is quite difficult to know the bidding price of specific keywords. In this paper, we compare analysis results of machine learning algorithms with various optimizers to find the targeted rank of specific keywords and the desired ranking on the online web searching platform by using the machine learning algorithms. Particularly, it is quite important to find an appropriate optimization mechanism for the machine learning algorithm because it can derive different results of the applied machine learning algorithm according to the optimization mechanism. Therefore, we propose an appropriate machine learning algorithm with various optimizers by analyzing the web-search-word advertisement data. The ANN of deep learning and regression (i.e., linear, logistic, softmax regressions) algorithms are applied for the machine learning algorithms. In addition, we applied the optimizer mechanisms of Adam, Adagrad, Gradient Descent, Momentum and RMSProp to these algorithms. Extensive simulation results show that the Adam and Adagrad optimizer mechanisms have high test accuracy rate. Specifically, it can be seen that each optimizer mechanism shows quite difference in accuracy rate according to learning rate. Finally, it is necessary to analyze the machine learning algorithm applying various optimizer mechanisms to present the bidding price prediction model of the web-search-word advertisement. In this paper, it makes it possible to predict the optimal bidding price for the web-search-word advertisement.Â Â